Phosphorus Alters Starch Morphology and Gene Expression Related to Starch Biosynthesis and Degradation in Wheat Grain - Zhang, Runqi; Li, Cheng; Fu, Kaiyong; Li, Chao; Li, Chunyan (Frontiers in Plant Science, 2018)
Phosphorus is an essential plant macronutrient which profoundly affects the yield and quality of wheat starch. In this study, scanning electron microscopy showed that P fertilizer amount (0, 46, and 92 kg P ha-1) had no significant effect on the shape of starch granules in wheat (cv. Xindong 20) grain. However, confocal laser scanning microscopy with 3-(4-carboxybenzoyl) quinoline-2-carboxaldehyde and methanolic merbromin stains indicated that P amount influenced the microstructure of the starch granules. Starch granules from the 46 kg P ha-1 treatment released significantly more reducing sugars than those from the 0 and 92 kg P ha-1 treatments during digestion with alpha-amylase and amyloglucosidase digestion. Phosphorus application (especially the 46 kg P ha-1 treatments) significantly increased the relative expression of genes related to starch synthesis (especially during early to mid-grain filling) and starch degradation (especially during mid- and late grain filling). Phosphorus application also increased the transcript abundance of amylase genes at the periphery of the endosperm. We propose that P application, especially the 46 kg P ha-1 treatment, enhanced channels in wheat starch granules. These channels facilitated the transport of substances required for starch biosynthesis, thus increasing starch accumulation in wheat endosperm. These results provide insight into the potential mechanisms through which P influences the microstructure and biosynthesis of wheat starch.